Women Facing Legal Cases: Reflection on the Use of Articles 284 and 285 of the Indonesian Criminal Code from the Experiences their Legal Counselor - Sandiata, Bella (Jurnal Perempuan, 2018)
This paper raises the narrative of experience from legal counselor who once accompanied women victim in cases related to article 284 of the Criminal Code on adultery and article 285 of the Criminal Code on rape. In an interview with the author, four female public lawyers shared their experiences including challenges and obstacles they encountered while advocating cases of adultery and rape. Unacceptable reports, slow-running legal process or even halt in the middle of the process, and facing the attitude of sexism towards victims and public lawyers are some of the obstacles and challenges experienced by the legal counselor of women victims. These public lawyers saw that the criminal law is still not on the side of women and has not provided justice for women. They directly see and experience the difficulty of the legal process running for the article of adultery and rape. Using the feminist legal theory this paper found that law that do not have a gender perspective and siding with women are obstacles to the fulfillment of women victims rights.